Sobreprotección de los padres de familia y tipo de personalidad de los estudiantes de la Unidad Educativa “Camilo Gallegos Toledo” - Puma Hidalgo, Elina Dayanara (2022)
This research was conducted at Unidad Educativa “Camilo Gallegos Toledo”, located in the city of Riobamba, province of Chimborazo. The objective was to determine the correlation between parental overprotection and students' personality of the ninth year Parallel "A" of General Basic Education of Unidad Educativa "Camilo Gallegos Toledo." The project had a quantitative approach, with a non-experimental design, the type of research was field research, for the cross-sectional time, for the descriptive and correlational level, as for the sample was stratified intentional, according to the interest of the research, composed of 33 students, 13 males, and 20 females. The psychometric test HSPQ (Adolescent Personality Questionnaire) by M.D. Cattell, Raymond B. Cattell was applied to the students, identifying factors of overprotection in the students, in addition to a structured questionnaire of 8 questions applied to the parents, The statistical program SPSS Pearson analysis of two variables was used to establish the relationship between the variables, obtaining; as a result, a correlation of 0.408*, with a significance of 0.017, which means that overprotection is related to students' personality of the ninth year Parallel "A" of GBE of Unidad Educativa "Camilo Gallegos Toledo," proving that overprotection reveals specific characteristics in students' personality.